Nutritional and Antinutritional Properties of Raw, Fermented, and Germinated Yellow Maize (Zea mays L.) (Lafia Journal of Scientific and Industrial Research, 2026)
This study evaluated nutritional and anti-nutritional qualities of raw (RM), fermented (FM), and germinated (GM) yellow maize (Zea mays) using traditional home methods. All analyses were performed according to standard procedures. Proximate analysis revealed that germination increased the fiber (10.19 g/100 g) and fat contents, whereas fermentation increased the crude protein (13.56 g/100 g) and carbohydrate (74.03 g/100 g) contents. Antinutrients varied with processing: total phenols decreased from 0.50% in raw maize (RM) to 0.05% in germinated maize (GM); phytate ranged from 289.87 to 450.56 mg/100 g; alkaloids ranged from 7.28 to 12.48%; and tannins ranged from 5.39 to 9.17 mg/100g. The total amino acid content was 82.18 (RM), 79.79 (FM), and 82.33 (GM) g/100 g of crude protein, with valine being the first-limiting amino acid. Germination improved protein quality, whereas fermentation reduced the presence of certain anti-nutrients and protein content. These findings demonstrate that both methods can enhance the nutritional value of maize, thereby supporting the development of an improved maize-based diet.
Keywords: Amino acid profile; Anti-nutritional; Fermentation; Germination; Yellow Maize